2012
DOI: 10.1111/j.1742-7843.2012.00896.x
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Soluble Matrix Metalloproteinase‐9 Inhibitor for Potential Treatment of Dry Eye Syndrome

Abstract: Dry eye syndrome (DES) or keratoconjunctivitis sicca is an eye disease caused by the chronic lack of lubrication and moisture of the eye. The pathogenesis of DES involves the over-expression and over-activity of corneal Matrix Metalloproteinase 9 (MMP-9). We propose herein a new, non-symptomatic approach for the treatment of DES based on the inhibition of MMP-9 by a new highly soluble molecule, designed as PES_103 that has been shown to inhibit MMP-9 both in vitro and in vivo. The efficacy of PES_103 in vivo a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…46 Additionally, other authors have shown in-vivo benefits of using MMP-9 inhibitors for restoring tear production. 47 In the present study we also found consistent associations between the increase in IL-1RA tear levels and the worsening of the corneal staining, in addition to the relationship between the decrease in Schirmer test and the increase of IL-6, IL-8 and MMP-9 tear levels. These findings provide more evidence (at least in SS patients) to support the relationship existing between the response of the lacrimal functional unit in terms of tear molecule secretion and the clinical signs commonly observed in the slit lamp examination.…”
Section: Discussionsupporting
confidence: 87%
“…46 Additionally, other authors have shown in-vivo benefits of using MMP-9 inhibitors for restoring tear production. 47 In the present study we also found consistent associations between the increase in IL-1RA tear levels and the worsening of the corneal staining, in addition to the relationship between the decrease in Schirmer test and the increase of IL-6, IL-8 and MMP-9 tear levels. These findings provide more evidence (at least in SS patients) to support the relationship existing between the response of the lacrimal functional unit in terms of tear molecule secretion and the clinical signs commonly observed in the slit lamp examination.…”
Section: Discussionsupporting
confidence: 87%
“…With administration of PES_103, both tear volume and MMP-9 activity were restored to physiological levels. 32 …”
Section: Mmp Levels With Dry Eye Treatmentmentioning
confidence: 99%
“…The function of MMP-9 in the onset of dry eye has received a great deal of attention [43], and researchers have proposed that MMP-9 might become a diagnostic marker of dry eye at the molecular level [44]. Recently, a study inhibited MMP-9 as a new target for dry eye treatment [45]. In addition, MMP-9 plays important roles in the onset of pterygium, it not only disrupts the epithelial barrier to facilitate the invasion of pterygium into a transparent cornea, but also promotes the development and postoperative recurrence of pterygium [7,21].…”
Section: Vegf Is a Core Factor In The Cross Talk Between Pterygium Anmentioning
confidence: 99%